Pengembangan Evaluasi Digital Menggunakan Kahoot pada Pembelajaran Pendidikan Pancasila di Kelas IV Sekolah Dasar - Putri, Agtania Yunisa; Putera, Rafhi Febryan; Rahmatina, Rahmatina; Ladiva, Hasmai Bungsu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to develop a digital assessment using Kahoot! in the Civics education learning of fourth-grade elementary school students that is valid, practical, and effective. The development model used is the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed digital assessment is validated by media experts, language experts, and question experts using a validation sheet in the form of a questionnaire. The practicality of the product is measured through teachers' and students' response questionnaires, while the effectiveness of the product is measured based on the improvement of students' learning outcomes after using the digital assessment media. Trials are conducted at SDN 29 Rantau Batu Pasar, the main research at SDN 26 Bukit Putus Dalam, and the effectiveness test at SDN 04 Lagan Gadang Hilir. The validation results show a validity level of 88% (media), 92% (language), and 88% (questions), all of which fall into the very valid category. The practicality level according to teachers and students is also very high, with respective percentages of 91.42% and 92.6% (trial), 94.28% and 95.8% (main research), and 95.71% and 96% (effectiveness test). The effectiveness results show an improvement in learning outcomes from 73.3% to 85.9%. Therefore, it can be concluded that the digital evaluation based on Kahoot! in Civics Education learning for fourth-grade elementary school students is proven to be valid, practical, and effective for use in the learning process.